The molecular chaperonin TF55 from the Thermophilic archaeon Sulfolobus solfataricus. A biochemical and structural characterization. - Knapp, S; Schmidt-Krey, I; Hebert, H; Bergman, T; Jörnvall, H; Ladenstein, R (1994)
The purification and characterization of a new type of thermostable chaperonin from the archaebacterium Sulfolobus solfataricus is described. The chaperonin forms a hetero-oligomeric complex of two different, but closely related, subunits, which we have assigned TF55-alpha and TF55-beta. Their N-terminal sequences and amino acid residue compositions are reported. Two-dimensional projections of the chaperonin have been reconstructed from electron microscopy images, showing a 9-fold symmetrical complex, about 17.5 nm in height and 16 nm in diameter, with a central cavity of 4.5 nm. The complex is resistant to denaturing agents at room temperature and only pH values lower than 2 lead to dissociation. The separated subunits do not reassemble spontaneously but require Mg2+ and ATP for complex formation. Both subunits are necessary for formation of the TF55 oligomer. Significant structural changes have been observed after phosphorylation, thus providing evidence for a structural mobility during the chaperonin-assisted folding process of a protein. The phosphorylation reaction is modulated by potassium and magnesium ions. Magnesium seems to have an inhibitory effect, whereas potassium enhances this reaction.